Takhrij and Syarah Hadith of Agrotechnology Study of the Benefits of Siwak for Dental and Oral Health - Gina Cintya; Wahyudin Darmalaksana; Dikayani Dikayani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study was to discuss the hadith of the Prophet Muhammad about the benefits of Siwak Salvadora Persica on oral health. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study are proven that miswak has various benefits for oral health. The conclusion of this study is that the virtue of using the siwak recommended by the Prophet Muhammad has many benefits for oral health